Low‐cost inkjet printing of thin‐film mullite structures. (22nd August 2021) - Žitňan, Michal; Müller, Lenka; Zub, Karina; Schubert, Ulrich S.; Galusek, Dušan; Wondraczek, Lothar
Abstract: A commodity inkjet printer was modified to print layered ceramic structures on stiff glass substrates, using inks in the form of sols with mullite stoichiometry. The sol composition was optimized in terms of ink viscosity, surface tension, and evaporation properties. The ink was then fed into a multi‐nozzle commodity printer head and deposited by ink‐jetting. Thin lines without bulges with a thickness of ∼1.8 μm with concave profile and a line width of ∼100 μm were successfully printed on fused silica substrates. The presence of mullite was confirmed by Raman spectroscopy and XRD after sintering of printed structures.